Effectiveness of Oral Semaglutide in Management of Type 2 Diabetes: A Real-World Study from India - Aditya Dutta; Shama Mahendru; Rutuja Sharma; Ambrish Mithal (Indian Journal of Endocrinology and Metabolism)
Introduction: Oral Semaglutide (Sema-o) is the first oral glucagon like peptide-1 receptor analogue (GLP-1RA) commercially available for the treatment of type 2 diabetes (T2D). This study aimed to evaluate the efficacy of Sema-o in patients with T2D when added to the existing therapy. Methods: This retrospective real-world study enrolled adult patients with diabetes taking Sema-o, with at least one follow-up (from February 2022 till October 2023). A proforma recorded baseline and follow-up date, medications, body composition, laboratory and clinical parameters. Data is presented as median (interquartile range) and was analysed using SPSS. Results: A total of 351 patients followed up once, while 56 patients had 4 follow-up visits. Baseline parameters were as follows: age 53 years (43–61), duration of diabetes 10 years (5–16), weight 91 kg (79–103), body mass index (BMI) 32.7 kg/m2 (29.3–36.6) and HbA1c 7.9% (6.9–9). The addition of Sema-o in the existing therapy for diabetes resulted in a significant reduction in HbA1c {follow-up: 1st 0.5%, 2nd 0.9%, 3rd 1.1% and 4th 1.1% (all, P < 0.001)} and % weight reduction {follow-up: 1st 2%, 2nd 3.3%, 3rd 4.1% and 4th 4.3% (all, P < 0.001)} from baseline. Reductions in BMI, glucose (fasting/post-prandial), lipids, liver enzymes and body composition parameters were significant. Gastro-intestinal side-effects (299 events in 52.4% of patients) were frequent. A total of 34/9.7% patients discontinued Sema-o. Conclusion: Intensification of existing therapy with Sema-o in obese patients with moderately uncontrolled diabetes proved to be an effective and relatively safe strategy. Achieving normoglycemia and reductions in weight, lipids and body fat/visceral fat with Sema-o may confer a much needed cardiometabolic benefit in these patients.